Photo Degradation of Solochrom Violet Dye by ZnO: Experimental and Theoretical Study (Baghdad Science Journal, 2024)
The present project involves photodegrading the dye solochrom violet under advanced oxidation techniques at (25 oC) temperature and UV light. Zinc Oxide (ZnO) and UV radiation at a wavelength of 580 nm were used to conduct the photocatalytic reaction of the solochrom violet dye. One of the factors looked into was the impact of the starting conditions. pH, the amount of original hydrogen peroxide, and the dye concentration time radiation were used. For hours, the kinetics and percentages of degradation were examined at various intervals. In general, it has been discovered that the photodegradation rates of the dye were greater when H2O2 and ZnO were combined with UV light. The best wavelength to use was determined. Modern oxidation techniques were proven to be very effective at degrading the majority of contaminants in wastewater. Using a spectrophotometer, the dye's photocatalytic browning was investigated. The theoretical calculation concentrated on the active site using the density functional theory technique and the Gaussian 09 program.